2020
DOI: 10.1002/wer.1451
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of reduction in risk from antibiotic resistance genes in laboratory wastewater by using O3, ultrasound, and autoclaving

Abstract: Biological laboratory wastewater containing both antibiotic‐resistant bacteria (ARB) and antibiotics is a potential source of antibiotic resistance genes (ARGs). Thus, we determined the efficacy of autoclaving, a common disinfection method, in eliminating 5 ARGs (sul1, sul2, tetW, tetM, amp) and the integrase‐encoding gene intI1 from laboratory wastewater. Autoclaving (15 min, 121°C) inactivated all bacteria including ARB, whereas ARGs persisted in the wastewater with limited reduction even after 60 min of tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…At present, various physical treatments (e.g., ultraviolet radiation, heat, and cold plasma) have been proposed as solutions to control various foodborne pathogens, including ARB, in the food system [8] , [9] . For example, recent studies have reported that a combination of physical treatments may lead to the synergistic inactivation of various pathogenic bacteria, including Escherichia coli , Listeria spp., and Staphylococcus aureus [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] . However, during bacterial inactivation, nucleic acids can be released from the dead bacteria into the food environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, various physical treatments (e.g., ultraviolet radiation, heat, and cold plasma) have been proposed as solutions to control various foodborne pathogens, including ARB, in the food system [8] , [9] . For example, recent studies have reported that a combination of physical treatments may lead to the synergistic inactivation of various pathogenic bacteria, including Escherichia coli , Listeria spp., and Staphylococcus aureus [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] . However, during bacterial inactivation, nucleic acids can be released from the dead bacteria into the food environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, the development of technologies to control various antibiotic resistance factors related to ARB is often neglected. Although some studies have been conducted to monitor ARB distribution and reduce the horizontal gene transfer (HGT) of released ARGs, strategies to inactivate both ARB and ARGs have not been widely studied so far [6] , [17] , [18] , [22] , [23] , [24] , [25] .…”
Section: Introductionmentioning
confidence: 99%
“…In literature, chlorine has been reported that may lead to initially attack proteins and peptidoglycan bound to the cell wall and the cell membrane and, subsequently, penetrate into the cell wall to reach cytoplasm and react with nucleic acids [3,63]. Additionally, not only chlorine but also ozone has been recently reported for its ability to destroy ARGs [64][65][66]. Ozone reacts with bacterial functional groups, such as amines or amino acids, and also attacks proteins, peptidoglycan and liposaccharides in the cell envelope [67,68].…”
Section: Log Removal Of Args= C T Final -C T Initialmentioning
confidence: 99%
“…As a result, the ozone-oxygen mixture stopped all the bacterial strains present [74]. Ozone treatments have also been proved to reduce antibiotic resistance genes and pathogenic bacteria in wastewater [73][74][75][76][77].…”
Section: Effects Of O 3 On S Typhimurium Inactivationmentioning
confidence: 99%